2015
DOI: 10.4038/engineer.v48i3.6840
|View full text |Cite
|
Sign up to set email alerts
|

Health hazards, risk and safety practices in construction sites – a review study

Abstract: This review attempts to identify the health hazards, risks and causes of poor safety practices in construction sites. In addition, the differences in safety practices in both developed and developing countries and methods to improve construction site safety are discussed. Effects of some health hazards are chronic while some are acute. Mostly reported acute health hazards are "workers fall from height" and "electric shocks", while mostly reported chronic health hazard is "exposure to hazardous substances". Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 14 publications
0
40
0
4
Order By: Relevance
“…Construction personnel were not aware of the fact that noise and vibration can cause harm as 42.5% gave correct answer. It was put forth by Vitharana, De Silva and De Silva (2015) that construction personnel need not only trainings but also actions in ensuring workers to use PPE when working in sites with high noise and vibration exposure. Vibration and noise produced from various activities on site would also be hazardous when workers are exposed to the situation too much leading to various health hazards such as hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Construction personnel were not aware of the fact that noise and vibration can cause harm as 42.5% gave correct answer. It was put forth by Vitharana, De Silva and De Silva (2015) that construction personnel need not only trainings but also actions in ensuring workers to use PPE when working in sites with high noise and vibration exposure. Vibration and noise produced from various activities on site would also be hazardous when workers are exposed to the situation too much leading to various health hazards such as hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it requires involvement from all stakeholders, including workers, construction companies, owners, designers, regulators and educators [4]. Research has shown that a lack of proactive and preventive measures such as workforce training, risk source identification and control, safety awareness and education have considerable influence in controlling risk and safety on site [5]. Given all these facts, teaching safety to experienced workers remains a challenge, which magnifies when it comes to teaching GenerationZ (GenZ) students about construction safety, as most of them lack the vital experience of working in a construction site.…”
Section: Background: History and Connection To Gen Z Studentsmentioning
confidence: 99%
“…(2) Decision is made about the strengths and weaknesses of a recent safety program using a safety audit, which is part of the company's safety program [29]. (3) Injury rate of recurrence, which is the number of lost-time injuries per million hours worked and assumed as a method of evaluating safety performance, is computed [30,31].…”
Section: Literature Review: Risk Analysis On Construction Sitesmentioning
confidence: 99%
“…(3) A normalized direct relation matrix is built on the basis of direct relation matrix using Equation (2).…”
Section: Fuzzy Dematel Approachmentioning
confidence: 99%
See 1 more Smart Citation